Local Retrofit of Reinforced Concrete Structures by the ACM System - Stefano Sorace; Gloria Terenzi; Elena Fuso (Buildings, 2021)
During the last decades, low architectural impact strategies have been increasingly adopted in the seismic retrofit of reinforced concrete structures. Among the emerging technologies in this field, the active lateral confinement of columns, beams, and beam-to-column joints is gaining growing attention thanks to the localization of the interventions only on the members in unsafe conditions, the resulting small increase in size, and the limited demolition required for installation. The study presented herein is focused on the application of a highly performing confinement technology, named as ACM (Active Confinement of Masonry), which was conceived more than twenty years ago in Italy for masonry structures, and then successfully applied to reinforced concrete ones. A representative case study is examined in detail herein, i.e., a school built in the early 1960s in the Friuli Venezia Giulia area in Italy. A seismic assessment analysis of the building is carried out in its current state, also supported by preliminary diagnostic investigations, which highlights several seismic deficiencies, especially in terms of shear response of columns and beams. Thus, a retrofit hypothesis based on the installation of the ACM system is proposed, which allows attaining a substantial improvement in the seismic response capacities, while maintaining limited architectural intrusion. A detailed description of the case study characteristics and a synthesis of the time-history seismic analyses developed in original conditions are presented in this article, along with the design criteria, drawings of the interventions, and an evaluation of the resulting performance enhancement in retrofitted configuration.